Analysis of the Sekincau Community Health Center's Health Service Marketing Strategy to Increase Patient Visits - Anggraini, Devi; Paramarta, Vip; Yuliaty, Farida (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Community health centers, as first-level health facilities, play a crucial role in providing health services to the community. Quality service products, affordable prices, easily accessible locations, appropriate promotions, and the use of technology in services are important factors contributing to increased patient visits. Based on the results of the literature review, it was found that effective marketing strategies can significantly increase patient visits. This study recommends that the Sekincau Community Health Center continue to improve service quality and implement a targeted and sustainable marketing strategy. The Community Health Center management should focus on service product quality, fair pricing, promotions that directly address community needs, and maximize the use of technology to increase patient satisfaction and visits. Thus, the Sekincau Community Health Center is expected to be able to consistently and sustainably increase patient visits.